(untitled) (CAHIERS MAGELLANES-NS, 2024)
"Green chemistry can be defined as the design of chemical products and processes that decrease or eliminate the use or generation of toxic and hazardous substances" - USEPA. The review article highlights the efforts of green chemistry, how the principles of green chemistry are helping the mankind towards sustainable and healthy environment on global level. Research based on green chemistry evolves eco-friendly methods for the preparation of packing peanuts, thermal receipts without toxic ink, advanced vanadium redox flow battery, eco-friendly dry cleaning, eco-friendly paints, medicines etc. Still it may take very long and great efforts to apply designs based on the green chemistry principles in each and every field. But Green Chemistry is a great and much required contribution towards making our mother earth and environment sustainable.